The objectives that will be used in this research are to find out the quality of PBBP and PBB-P2, the contribution of PBB and PBB-P2 and the administration of PBB and PBB-P2 services. The type of research that will be carried out is qualitative descriptiv - Ahmad Mukoffi (Universitas Prof.Hazairin,SH Bengkulu, 2021)
The objectives that will be used in this research are to find out the quality of PBBP and PBB-P2, the contribution of PBB and PBB-P2 and the administration of PBB and PBB-P2 services. The type of research that will be carried out is qualitative descriptive, this research was conducted at the City Regional Revenue Agency. Malang is located on Jl. Major General Sungkono No. 82, Wonokoyo, Kec. Kedungkandanga, Malang City, East Java. Data collection techniques are interviews, documentation and observation, the data used are secondary and primary data, while the techniques in analyzing data are data reduction, PBB calculations. The results of this research state that there is an important relationship when implementing a policy in achieving revenue realization against a PBB revenue target and rural buildings as well as in offices and administrative management that makes the best payments and makes collections for PBB and BPPP.